MODEL PEMBERDAYAAN EKONOMI MASYARAKAT PESISIR (Studi Kasus Kegiatan Pembenihan Ikan Kerapu Hatchery Sekala Rumah Tangga / HSRT di Kabupaten Situbondo) - Ardy Soesanto (Faculty of Social and Political Science, 2016)
Indonesia is acountry that has the potential of marine natural resources is quite large, especially in the field of fisheries, But until now the condition of coastal communities still lagging. Therefore needed coastal zone management strategy right, one is to applay the model of economic empowerment of coastal communities in accordance with the region in natural resources and human resources cultere of the society. The research focus is on the implementation of the model of community empowerment through business activities grouper HSRT in Situbondo District that implement the principles of good governace. Empowerment model with the principles is that promotes involvement in the implementation of the three pilars, namely the role of goverment, private and public, aplication of the empowerment model was considered successful in the empowering the well-being of coastal communities reseach area. So that this model can be applied, then we describe the factors supporting and factor constraints and requirements that must be fulfiled. We hope this research can be used as the basis for local governments to adopt policies, as well as for further research.